Evidence for a More Disrupted Immune-Endocrine Relation and Cortisol Immunologic Influences in the Context of Tuberculosis and Type 2 Diabetes Comorbidity - Fernández, Rocío D. V.; Díaz, Ariana; Bongiovanni, Bettina; Gallucci, Georgina; Bértola, Diego; Gardeñez, Walter; Lioi, Susana; Bertolin, Yésica; Galliano, Romina; Bay, María L.; Bottasso, Oscar; D'Attilio, Luciano (Frontiers in Endocrinology, 2020)
Pulmonary tuberculosis (PTB), caused by Mycobacterium tuberculosis (Mtb), is a major health problem worldwide, further aggravated by the convergence of type 2 diabetes mellitus (DM) which constitutes an important risk factor for TB development. The worse scenario of patients with PTB and DM may be partly related to a more unbalanced defensive response. As such, newly diagnosed PTB patients with DM (TB+DM, n = 11) or not (TB, n = 21), as well as DM (n = 18) patients and pair matched controls (Co, n = 22), were investigated for the circulating immuno-endocrine-metabolic profile (ELISA), along with studies in peripheral blood mononuclear cells (PBMC) analyzing transcript expression (RT-qPCR) of mediators involved in glucocorticoid functionality. Given the hyperglycemic/hypercortisolemic scenario of TB+DM patients, PBMC were also exposed to stress-related cortisol concentrations (0.1 and 1 μM) and supraphysiologic glucose doses (10, 20, and 40 mM) and assessed for the specific response against Mtb stimulation (lymphoproliferation, -thymidine incorporation-, and cytokine production -bead-cytometry). All TB patients displayed increased plasma amounts of cortisol, growth hormone -hGH-, and proinflammatory mediators. In turn, TB+DM showed even higher levels of interferon gamma -IFN-γ- and hGH (vs. TB), or IL-6, C reactive protein, cortisol and hGH (vs. DM). Both DM groups had equally augmented values of IL-10. All TB patients showed decreased dehydroepiandrosterone- sulfate concentrations, even more in TB+DM cases. Leptin was also decreased in both TB cases, particularly in the TB group, revealing a lower body mass index, as well. Unlike PBMC from TB cases showing a decreased relationship between the glucocorticoids receptor (GR) isoforms (GRα/GRβ; functional isoform/negative isoform), cells from TB+DM patients had no changes in this regard, along with an increased expression of 11-beta hydroxysteroid dehydrogenase type-1, the enzyme facilitating intracellular cortisone to cortisol conversion. TB+DM patients also showed an increased Mtb antigen-driven lymphoproliferation. Compared to TB, DM and HCo counterparts, PBMC from TB+DM patients had a biased Th1 response to Mtb stimulation (increased IL-2 and IFN-γ production), even when exposed to inhibitory cortisol doses. TB+DM patients show a more unbalanced immuno-endocrine relationship, respect the non-diabetic counterparts, with a relative deficiency of cortisol immunomodulatory influences, despite their more favorable microenvironment for cortisol-mediated immune effects.